Effects of chick separation and feeding on the performance of hens and chicks - Amin, MJR; Howlider, MAR; Ali, MA (Bangladesh Veterinarian, 2010)
A study was conducted to observe the effect of separating chicks from broody hens after hatching, and supplementary feeding, on the performance of broody hens and chicks. Eighteen broody hens incubated 360 eggs of native hens. Broody hens and chicks were divided into three treatment groups; in T1, chicks were not separated, and chicks scavenged with mothers; in T2, chicks were separated at five days and fed ad libitum; and in T3, chicks were separated at 10 days and fed ad libitum. Hens in T2 and T3 received 50g feed/hen/day. The interval between end of incubation and first lay was shorter in T2 (36.3 days) and T3 (41.7) than in T1 (55.2). Clutch length was shortest in T1 (12.7 days), medium in T3 (15.0) and longest in T2 (17.0). There were more eggs/clutch in T2 (14.7) and T3 (14.3) than in T1 (11.5). There were no differences in broody hen's body weight between treatment groups. Mortality of chicks was highest in T2 (39.6%), medium in T3 (33.9), and lowest in T1 (21.0). Body weight of chicks was highest in T2, medium in T3 and lowest in T1, except at 1st week of age. It is suggested that separation of chicks and supplementary feeding was beneficial in terms of interval between end of incubation and first lay, clutch length, number of eggs per clutch and body weight of chicks. DOI: 10.3329/bvet.v26i1.4626 Bangl. vet. 2009. Vol. 26, No. 1, 13-16